Assessment of agroeconomic indices in polycultures of lettuce, rocket and carrot through uni- and multivariate approaches in semi-arid Brazil - Neto, Francisco Bezerra; Porto, Vania Christina N.; Gomes, Eliane G.; Cecilio Filho, Arthur B. [UNESP]; Moreira, Joserlan N. (Elsevier B.V., 2012)
The polyculture among vegetables is an activity that to have good results, needs a proper planning. Although it often requires more labor, has several advantages over monoculture, among them is that polycultures are generally are more productive, provide with productivity of various plant constituents and a more balanced human diet, contribute to economic return, economic and yield stability, social benefits and farmer's direct participation in decision-making. The objective of this study was to evaluate agroeconomic indices of polycultures derived from the combination of two cultivars of lettuce with two cultivars of rocket in two cultures strip-intercropped with carrot cultivar 'Brasilia' through uni-multivariate approaches in semi-arid Brazil. The experimental design used was of randomized complete blocks with five replications and the treatments arranged in a factorial scheme of 2 x 2. The treatments consisted of the combination of two lettuce cultivars (Baba de Verao and Taina) with two rocket cultivars (Cultivada and Folha Larga) in two cultures associated with carrot cv. Brasilia. hi each block were grown plots with two lettuce cultivars and two rocket cultivars, and carrot in sole crop. In each system was determined the lettuce leaf yield, rocket green mass yield and carrot commercial yield. Agrieconomic indices such as operational cost, gross and net income, monetary advantage, rate of return, profit margin, land equivalent ratio and yield efficiency for DEA were used to measure the efficiency of intercropping systems. In the bicropping of lettuce and rocket associated with carrot cv. 'Brasilia', suggests the use of lettuce cultivar 'Taina' combined with rocket cultivars 'Cultivada' or 'Folha Larga'. It was observed significant effect of lettuce cultivars in the evaluation of polycultures of lettuce, carrot and rocket, with strong expression for the lettuce cultivar 'Taina'. Both uni- and multivariate approaches were effective in the discrimination of the best polycultures. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Lactuca sativa; Daucus carota; Eruca sativa; Agronomic and economic indicators; Multivariate analysis